The role and significance of cradle in Kazakh and Turkic culture (Journal of Philosophy, Culture and Political Science, 2025)
The research article is devoted to historical place, past and present changes of a cradle as a branch of the Kazakh and Turkish woodworking art and a symbol of cultural traditions of these peoples. A cradle as an object of material culture is not only an everyday simple item, but also a symbolic culture that transmits sacred information about worldview and traditions of the people between generations. In the context of globalization and changes in traditional lifestyles, the study of the cradle allows us to preserve historical and cultural data related to it and assess the role of material culture in modern society. This demonstrates the relevance of this research. In this context, the study examines woodworking art and cradle-making of the Kazakh and Turkish peoples in three different aspects: ancient techniques and methods of cradle-making as a branch of woodworking art of the Kazakh and Turkic peoples; features of the Kazakh and Turkish craftsman in decoration techniques and equipment of a cradle; the place of cradle in history and culture of the Kazakh and Turkish peoples: past and present. During the study of these aspects, the ethnographic research method, including content analysis and interview methods, was used. As a result, it was found that although the Kazakh and Turkish peoples were descended from the ancient Turkic culture, the processes of colonization and globalization experienced by them have different effects on preservation of a cradle as a cultural heritage. Scientific significance of the study: Information and analyzed conclusions regarding traditional and modern techniques and methods of making and decorating cradles by Kazakh and Turkic craftsmen, as well as their place in the history and culture of these two peoples are extremely useful for researchers in the field of ethnography and cultural studies. In addition, a content analysis was conducted on peculiarities of making and decorating cradles inherited from the Kazakh and Turkic ancestors, on features of use of Kazakh and Turkish ornaments and semiotic patterns, revealed by the research, and specific practical recommendations have been prepared regarding ornaments to be placed on cradles. These recommendations can be used by modern cradle-making craftsmen as a guide for finishing and decorating cradles. This demonstrates the practical importance of the work.Keywords: woodworking art, cradle, ethnographic research, material culture, cultural studies.